1994
DOI: 10.1021/np50108a017
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Constituents of Baccharis gaudichaudiana

Abstract: Three new labdane diterpenes, gaudichaudols A-C [1-3], a new clerodane diterpenoid, gaudichaudone [4], and the known clerodane, articulin acetate [5] have been isolated from the aerial parts of Baccharis gaudichaudiana, together with the known compounds, apigenin, hispidulin, spathulenol, and ursolic acid. Through the application of 1D- and 2D nmr spectroscopy, the structures of the new diterpenoids [1-4] were, in turn; elucidated as 15,16,18,19-tetrahydroxylabd-5-ene, 15-O-acetyl-16,18,19-trihydroxylabd-5-ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 13 publications
2
39
0
4
Order By: Relevance
“…Despite not being preponderant, the oil analyses showed that among its numerous constituents, there are some components described in literature as cytotoxic substances against tumoral cells, such as β-caryophyllene (5.9%), β-elemene (3.1%), δ -elemene (1.6%), α-humulene (2.3%) (Duh et al, 1999;Legault et al, 2003;Sibanda et al, 2004;Sylvestre et al, 2005;Stravi et al, 2005;Tatman and Mo, 2002;Wang et al, 2005;Sylvestre et al, 2006;Hou et al, 2006;Tao et al, 2006;Xiao et al, 2006. Some other components with no or low antitumoral activity were also found in this species, eg sphathulenol (3.8%), á-pinene (6.4%), linalool (0.5%), myrcene (0.6%) (Fullas et al, 1994;Tatman & Mo, 2002;Stavri et al, 2005).…”
Section: Introductionmentioning
confidence: 82%
“…Despite not being preponderant, the oil analyses showed that among its numerous constituents, there are some components described in literature as cytotoxic substances against tumoral cells, such as β-caryophyllene (5.9%), β-elemene (3.1%), δ -elemene (1.6%), α-humulene (2.3%) (Duh et al, 1999;Legault et al, 2003;Sibanda et al, 2004;Sylvestre et al, 2005;Stravi et al, 2005;Tatman and Mo, 2002;Wang et al, 2005;Sylvestre et al, 2006;Hou et al, 2006;Tao et al, 2006;Xiao et al, 2006. Some other components with no or low antitumoral activity were also found in this species, eg sphathulenol (3.8%), á-pinene (6.4%), linalool (0.5%), myrcene (0.6%) (Fullas et al, 1994;Tatman & Mo, 2002;Stavri et al, 2005).…”
Section: Introductionmentioning
confidence: 82%
“…Alguns compostos isolados de B. gaudichaudiana foram testados em células com leucemia linfocítica P-388, bem como em uma seqüência de linhagem de células humanas. Entre os diterpenóides testados, os labdanos gaudichaudols A-C [6, 7, 8], os clerodanos gaudichaudona [9] e acetato de articulina [10] mostraram significante atividade citotóxica contra algumas células testadas 49 . A partir das folhas de B. lejia foram isolados uma série de neo-clerodanos com importante toxicidade para Artemia salina.…”
Section: Aspectos Econômicosunclassified
“…Depending on its diterpenoids composition (gaudichaudiosides), it may have different taste properties, from sweet to bitter or neutral. 4 B. microcephala (Less.) DC.…”
Section: Introductionmentioning
confidence: 99%